A comparative study to evaluate the safety & efficacy of Etoricoxib and Piroxicam in pharmacotherapy of Osteoarthritis in tertiary care hospital Kanpur - Princ Bgheal; Dr. Nilam Nigam; Dr. Kriti Jalota (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background:Osteoarthritis (OA) is a common degenerative joint disorder characterized by chronic pain and functional limitation. This study aimed to compare the efficacy, safety, and tolerability of Etoricoxib and Piroxicam in patients with symptomatic OA.Methods:A prospective, open-label, longitudinal study was conducted at Rama Medical College, Kanpur, involving 284 patients randomized equally into two groups: Group A (Etoricoxib) and Group B (Piroxicam). Clinical outcomes were assessed using the Visual Analogue Scale (VAS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) at baseline, Day 7, and Day 15. Safety evaluation included CRP levels, liver and renal function tests, complete blood count, and monitoring of adverse effects.Results:Both groups showed significant improvement in VAS and WOMAC scores over 15 days. However, Group A demonstrated significantly greater reductions at Day 7 and Day 15 (p < 0.01), indicating superior symptom control. CRP levels and organ function tests remained comparable between the groups (p > 0.05), suggesting similar safety profiles. Adverse effects were significantly lower in Group A, particularly for gastric discomfort (p = 0.005) and vomiting (p = 0.044), with a lower overall incidence of side effects (mean 5.42 ± 2.71 vs. 7.58 ± 5.73).Conclusion:Etoricoxib provided more effective and better-tolerated short-term symptom relief in osteoarthritis patients compared to Piroxicam, with a comparable safety profile. These findings support its use as a preferable option for short-term management of OA symptoms.